Testing DAT1 and DRD4 Genes in Attention Deficit Hyperactivity Disorder Using a Wide Spectrum of Neurocognitive Batteries - Ünsel-Bolat, Gül; Bolat, Hilmi; Yıldırım, Sema; Özgül, Semiha; Tahıllıoğlu, Akın; Yazıcı, Kemal Utku; Ercan, Eyüp S. (John Wiley and Sons Inc, 2026)
Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental condition characterized by marked heterogeneity in cognitive functioning. This study aimed to examine the associations between polymorphisms in the DAT1 and DRD4 genes and neurocognitive performance in children and adolescents with ADHD. A total of 336 participants aged 6–18 years (244 with ADHD and 92 healthy controls) were included. Variable number tandem repeat (VNTR) polymorphisms in the 3? UTR of DAT1 and exon 3 of DRD4 were genotyped. Neurocognitive performance was assessed using standardized scores derived from the CNS Vital Signs battery. Associations between genotypes and cognitive domains were examined using analysis of covariance (ANCOVA), adjusting for age and gender. Homozygosity for the DRD4 4-repeat allele was significantly associated with poorer cognitive flexibility, whereas a trend-level difference was observed for complex attention. In contrast, DAT1 10R/10R homozygosity and DRD4 7-repeat allele carriage were not associated with significant differences in reaction time, complex attention or cognitive flexibility. These findings suggest that DRD4, rather than DAT1, may represent a more salient dopaminergic genetic marker of executive dysfunction in ADHD. The results underscore the domain-specific and modest nature of genetic influences on cognition and highlight the importance of integrating genetic markers with cognitive endophenotypes to better characterize heterogeneity in ADHD. © 2026 The Author(s). International Journal of Developmental Neuroscience published by Wiley Periodicals LLC on behalf of International Society for Developmental Neuroscience.
Keywords: ADHD; DAT1; dopamine; DRD4; genotype; neurocognitive function; VNTR